2005
DOI: 10.1897/03-652.1
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing effects of pesticides on invertebrate communities in streams

Abstract: The aim of this investigation was to find patterns in aquatic invertebrate community composition that are related to the effects of pesticides. Investigations were carried out in 20 central European streams. To reduce the site-specific variation of community descriptors due to environmental factors other than pesticides, species were classified and grouped according to their vulnerability to pesticides. They were classified as species at risk (SPEAR) and species not at risk (SPEnotAR). Ecological traits used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
497
4
11

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 605 publications
(555 citation statements)
references
References 38 publications
21
497
4
11
Order By: Relevance
“…For example, Wiberg-Larsen (2004) created a database on the larval head width, first and last week as well as duration of the flight period (all numeric descriptions) and the functional feeding groups (categorical descriptions) of Danish caddisfly species to relate these traits to stream width and the presence of a riparian forest. Likewise, Liess & Von der Ohe (2005) created a database at the species level including three biological traits (generation time, migration ability and aquatic stages in summer) of many European invertebrates to assess their risk of being affected by pesticides. Finally, Baird & Van den Brink (2007) started to assemble species traits of freshwater invertebrates to use them in predictions of species sensitivity to toxic substances.…”
Section: Technical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Wiberg-Larsen (2004) created a database on the larval head width, first and last week as well as duration of the flight period (all numeric descriptions) and the functional feeding groups (categorical descriptions) of Danish caddisfly species to relate these traits to stream width and the presence of a riparian forest. Likewise, Liess & Von der Ohe (2005) created a database at the species level including three biological traits (generation time, migration ability and aquatic stages in summer) of many European invertebrates to assess their risk of being affected by pesticides. Finally, Baird & Van den Brink (2007) started to assemble species traits of freshwater invertebrates to use them in predictions of species sensitivity to toxic substances.…”
Section: Technical Frameworkmentioning
confidence: 99%
“…Combining information on physiological sensitivity to organic toxicants and life-history traits indicating the recovery potential of invertebrates provided a database for the large-scale assessment of pesticide stress on stream systems (Liess & Von der Ohe, 2005). Von der Ohe et al…”
Section: Literature-derived Evidence For Stream Invertebratesmentioning
confidence: 99%
“…For a practical application in ERA, the vulnerability concept should be expressed in quantitative terms. Some tools capable of quantifying the vulnerability to specific stress factors have already been developed and proposed, particularly for freshwater ecosystems [48,49]. The development, application and validation of methods capable of assessing the vulnerability of aquatic and terrestrial ecosystems to different kinds of stressors is a priority for research.…”
Section: Ecosystem Vulnerabilitymentioning
confidence: 99%
“…This approach was adopted to study the effects of toxic contamination on invertebrate communities in running waters [15][16][17]. It was shown that tolerant taxa are characterized by resistance and resilience traits [e.g., high mobility (which permits avoidance of exposition and dispersion) and short life cycles (which allow rapid re-colonization after disturbance)].…”
Section: Community Functioning: Species Traitsmentioning
confidence: 99%
“…Riverine invertebrate communities have been extensively studied in response to gradients of contamination, producing effective toxicity indices [15][16][17]. By contrast, benthic communities in lakes have still been rather neglected, since the ecological status of lentic ecosystems has for long been assessed on the basis of only chemical and physical parameters.…”
Section: Introductionmentioning
confidence: 99%